Evaluasi Implementasi Nilai-Nilai Cinta dalam Proses Pembelajaran: Perspektif Pendidikan Humanis - Nurfadhilah Nur; Kasmah; Astuti (Jurusan Tarbiyah STAI Al-Gazali Bone, 2026)
Humanistic education and the Love-Based Curriculum (Kurikulum Berbasis Cinta/KBC) emphasize the holistic development of students by creating an empathetic, safe, and humanizing learning environment. This study aims to evaluate the implementation of love-based values in the learning process at MAN 2 Bone from the perspective of humanistic education. The evaluation addresses three main questions: how love values are implemented in classroom learning, the extent to which this implementation reflects humanistic education principles, and the supporting and inhibiting factors involved. A qualitative approach with a case study design was employed at MAN 2 Bone. Data were collected through in-depth interviews with school administrators, teachers, and students; direct classroom observations; and documentation analysis of lesson plans and school program documents. The data were analyzed thematically, covering dimensions of love for God, self and others, knowledge, the environment, and the nation. Findings reveal that MAN 2 Bone possesses strong foundational support for implementing love values, evidenced by its National Adiwiyata environmental culture, experience with project-based learning (P5), and participation in KBC technical guidance. The implementation is manifested through the teacher's role as a facilitator providing psychological safety, empathetic communication, active student engagement, and holistic process-oriented assessment. However, key challenges include varying conceptual understandings among teachers and the risk of reducing KBC into mere administrative compliance. The study concludes that the success of KBC relies on substantive pedagogical transformation in daily classroom interactions rather than administrative labeling of curriculum documents.